Penggunaan Digital Marketing Dalam Mengembangkan UMKM di Kelurahan Medokan Semampir - Ega Rizqita Vitrani; Yanda Bara Kusuma (Madani: Jurnal Ilmiah Multidisiplin, 2023)
Digital marketing is one of the marketing methods used by MSME actors to develop their business. The increasing use of the internet makes people do modern marketing and leave conventional marketing methods. Digital marketing is a wider promotion and market search effort by utilizing several online media. The online marketing process can make it easier for consumers to find and get information about the product they are looking for. Digital marketing can also make it easier for MSMEs to market their products quickly and precisely. It is known that MSME actors have not implemented it optimally, especially the lack of knowledge about the importance of digital marketing. Through this community service, by providing training and assistance regarding digital marketing to MSMEs, it is hoped that this can become knowledge and knowledge for MSMEs in developing their business.